CLIC6’s role in cancer: from broad analysis to breast cancer validation - Wang, Junyi; Wang, Yiyang; Ma, Haotian; Li, Yongxiang; Hou, Jiayue; Li, Jiaqi; Ismtula, Dilimulati; Guo, Chenming (Frontiers in Oncology, 2025)
BackgroundChloride Intracellular Channel 6 (CLIC6) is a potential cancer therapy target due to its close association with tumor development. However, its diagnostic and prognostic roles, as well as its impact on immune regulation in different cancers, remain unclear.MethodsThis study utilized public databases like TCGA and GEO to analyze CLIC6 expression, diagnostic value, and prognostic significance across various cancers. It examined genetic and epigenetic variations, immune correlations, and performed functional enrichment analysis to uncover CLIC6-related pathways. Western blotting confirmed CLIC6 protein levels in breast cancer samples, while CCK-8, colony formation, transwell, and scratch assays evaluated its role in cell proliferation and migration. Tissue microarray and immunohistochemistry further validated CLIC6 expression in breast cancer.ResultsResearch shows that CLIC6 expression is typically lower in most cancers compared to normal tissues, with distinct patterns across different stages. It serves as a useful diagnostic marker and potential prognostic factor for BRCA, LUAD, STAD, and LGG. CLIC6 mutations are common in many cancers and affect prognosis. In most tumors, CLIC6 expression correlates with m6A methylation, and its promoter is highly methylated. In BRCA, the expression of CLIC6 is related to bacterial defense, immune response, endopeptidase regulation, neuropeptide signaling, and amino acid transport. It is expressed at low levels in BRCA tissues, and we speculate that a higher CLIC6 expression may be protective.ConclusionIn conclusion, CLIC6 can serve as a key biomarker for various cancers, and its expression level is related to the tumor immune microenvironment and the outcomes in selected cancers; further validation is warranted. Our research on CLIC6 in BRCA has revealed new potential for tumor treatment strategies targeting this marker.